Najkrótszy przewodnik po moim ojcu. Z Martą Herling rozmawia Magdalena Śniedziewska - Śniedziewska, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The interview is devoted to Gustaw Herling-Grudziński. The writer’s daughter, Marta, talks about her father, particularly focusing on the Italian contexts of his biography and writings. Also discussed is the problem of the writer’s attitude towards the Italian language and the reception of his works in Italy. Another important topic is Naples as a fascinating source of writing inspirations and, at the same time, the city where Herling-Grudziński happened to live and die.